The eco of Barthes’ photography. The new lucid camera: Notes about digital camera (Communication & Society, 2011)
Thirty years ago Roland Barthes looked for a third level of reading images which distanced itself from rigid informative and symbolic reading in order to allow the signifier to talk. His analysis received better notoriety in the study of photography La chambre claire. This article makes the hypothesis that what Barthes left on his notes about the photographic medium resounds nowadays on one hand in the miniaturization of resources and the instantaneity of the digital video camera medium and, on the other hand, on the principle of modulation and accessibility of new media. Subsequently, the text examines the notion of barthanian memory and the parallelism that this one takes together with the reflections that Jean-Luc Godard granted through the electronic image. The apparent arbitrariness in the selection of images that integrate this study continues Barthes’ analysis according to a criterion of the author’s confidence in spontaneity and memory.